2000
DOI: 10.1063/1.125977
|View full text |Cite
|
Sign up to set email alerts
|

Microwave properties of tetragonally distorted (Ba0.5Sr0.5)TiO3 thin films

Abstract: A strong correlation is observed between the structure and the microwave dielectric properties of epitaxial Ba0.5Sr0.5TiO3 (BST) thin films deposited onto (001) MgO by pulsed laser deposition. Films were deposited at 750 °C in an oxygen pressure that was varied from 3 to 1000 mTorr. The tetragonal distortion (ratio of in-plane and surface normal lattice parameters, D=a/c) of the films depends on the oxygen deposition pressure. D varied from 0.996 at 3 mTorr to 1.003 at 800 mTorr. At microwave frequencies (1–20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
154
1
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 275 publications
(160 citation statements)
references
References 12 publications
4
154
1
1
Order By: Relevance
“…3 Numerous studies have shown that incorporating small amount of aliovalent (e.g., Mg 2þ 4 , La 3þ 5 , Al 3þ 6 , Ce 3þ 7 , Nb 5þ 6,8 ) or isovalent (e.g., Zr 4þ , Sn 4þ , Ge 4þ 9 ) ions into a BST lattice effectively modifies the dielectric properties (tunability, dielectric loss, and leakage current (LC)) of the BST film. 10 Mg 2þ and Nb 5þ , which are acting as an electron accepter and donor, respectively, by replacing the B site of the (A 2þ B 4þ O 2þ 3 ) perovskite, have received the most attention because of their drastic effect in altering the dielectric properties of the BST film.…”
Section: Introductionmentioning
confidence: 99%
“…3 Numerous studies have shown that incorporating small amount of aliovalent (e.g., Mg 2þ 4 , La 3þ 5 , Al 3þ 6 , Ce 3þ 7 , Nb 5þ 6,8 ) or isovalent (e.g., Zr 4þ , Sn 4þ , Ge 4þ 9 ) ions into a BST lattice effectively modifies the dielectric properties (tunability, dielectric loss, and leakage current (LC)) of the BST film. 10 Mg 2þ and Nb 5þ , which are acting as an electron accepter and donor, respectively, by replacing the B site of the (A 2þ B 4þ O 2þ 3 ) perovskite, have received the most attention because of their drastic effect in altering the dielectric properties of the BST film.…”
Section: Introductionmentioning
confidence: 99%
“…10'bar), la constante diélectrique mesurée à 12, 5 GHz est de 1114. Cette valeur est à comparer à E = 500 à 10 GHz obtenu par Kim et al [4] pour des films de BaSrTiO, de 300 nm seulement.…”
Section: Obtention De Films Mono-orientés De Forte éPaisseurunclassified
“…In the recent past, BST-based thin films for RF/microwave applications have been deposited on ceramic (MgO, LaAlO 3 , SrTiO 3 ) and a variety of other designer substrates. [141][142][143][144][145][146][147][148] Major drawbacks of these substrates are the high cost of the ceramic substrates and the fact that ceramic substrates, such as MgO, LaAlO 3 , and SrTiO 3 , are only available in small size geometries (2 in. wafers) which are not suitable for large-area film deposition.…”
Section: Substrates and Packaging Considerationsmentioning
confidence: 99%